Afghanistan’s Islam: From Conversion to the Taliban (University of California Press, 2016)
This book provides the first overview of the history and development of Islam in Afghanistan. Written by leading international experts, chapters cover every era from the conversion of Afghanistan through the medieval period to the present day. Based on primary sources in Arabic, Persian, Pashto, Uzbek, and Urdu, its depth of coverage is unrivalled in providing a developmental picture of Afghanistan’s Islam, including such issues as the rise of Sufism, women’s religiosity, state religious policies, and transnational Islamism. Looking beyond the unifying rhetoric of theology, the book reveals the disparate and contested forms of Afghanistan’s Islam